THE EFFECTS OF DEPOSIT TO ASSET RATIO ON THE FINANCIAL SUSTAINABILITY OF DEPOSIT TAKING MICRO FINANCE INSTITUTIONS IN KENYA - Mwangi, Maryanne; Muturi, Willy; Ombuki, Charles (International Journal of Economics, Commerce and Management, 2015)
Explanatory research design was used for the purpose of this study. The target population was the 9 registered Micro Finance Banks regulated by the Central bank of Kenya where a populous sample was selected for the purposes of the study. The study utilized cross sectional data set up to draw inferences on the study using SPSS statistical package. The study found deposit to asset ratio to be statistically significant in determining the financial sustainability of MFIs (t values=2.374, p values=0.0005). Therefore this study calls for the development of appropriate regulatory policies that enable MFIs to have access to cheaper long term debt to improve their profitability. The study also calls for listing of the MFIs to list on the GEM segment of the capital markets.
Keywords: Deposit; Asset Ratio; Financial Sustainability; Micro Finance Institutions